Coal Dust Exposures Change the Spiral Artery Remodeling and Natural Killer Cells Counts in the Uterus of Pregnant Rats - Wasilah, Siti; Soeatmadji, Djoko W.; Sardjono, Teguh Wahju; Kania, Nia; Noor, Meitria S. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Indonesia has numerous coal resources, but the effects of environmental pollution by coal dust to human health, especially the reproductive system, are still less investigated. Chronic coal exposures during pregnancy might cause systemic and uterine inflammation that induces disturbances of spiral artery remodeling. AIM: This research was conducted to analyze the effect of coal dust exposures to uterine spiral artery remodeling and natural killer (NK) cell counts. METHODS: There were 42 female adult Rattus norvegicus rats which had been simultaneously mated after synchronization of estrous cycle used as animal subjects. The rats then divided into seven groups, those were K0 (without exposure); K1-1, K1-2, K1-3; and K2-1, K2-2, K2-3 which were exposed to 6.25 mg/m3, 12.5 mg/m3, and 25 mg/m3 dose for 1 h (K1) and 2 h (K2) per day, respectively. The rats were exposed by a dust exposure machine (NKBS-1-2010- 0.5) every morning starting from the day-1 to day-19 post-mating and were sacrificed on day-19 afternoon. All uterus lobes of each pregnant rat were taken and histologically processed by HE staining. Five histological slides were randomly taken as samples representing each pregnant rat and were examined for ten visual fields per slide for the measurements of diameter and wall thickness of spiral arteries. NK cells were observed immunobiological. Data analyses used Kruskal–Wallis. RESULTS: Result showed that there were significant differences of diameters and wall thickness of spiral arteries and uterine NK cells in all exposed groups compared to control (P < 0.05). Diameter and wall thickness of spiral arteries were thicker in coal dust exposure than normal pregnant rats. NK cell number was more in coal dust exposure than normal pregnant. CONCLUSION: Coal dust exposures caused the thickening of wall and narrowing of lumen of spiral arteries and NK cell counts that might influence pregnancy.